Physical Exercise−Mediated Changes in Redox Profile Contribute to Muscle Remodeling After Passive Hand-Rolled Cornhusk Cigarette Smoke Exposure - Thirupathi, Anand; Scarparo, Silvia; Silva, Paulo L.; Marqueze, Luis F.; Vasconcelos, Franciane T. F.; Nagashima, Seigo; Cunha, Eduardo B. B.; de Noronha, Lúcia; Silveira, Paulo C. L.; Nesi, Renata T.; Gu, Yaodong; Pinho, Ricardo A. (Frontiers in Physiology, 2020)
Consumption of non-traditional cigarettes has increased considerably worldwide, and they can induce skeletal muscle dysfunction. Physical exercise has been demonstrated to be important for prevention and treatment of smoking-related diseases. Therfore, the aim of this study was to investigate the effects of combined physical exercise (aerobic plus resistance exercise) on muscle histoarchitecture and oxidative stress in the animals exposed chronically to smoke from hand-rolled cornhusk cigarette (HRCC). Male Swiss mice were exposed to ambient air or passively to the smoke of 12 cigarettes over three daily sessions (four cigarettes per session) for 30 consecutive days with or without combined physical training. 48 h after the last training session, total leukocyte count was measured in bronchoalveolar lavage fluid (BALF), and the quadriceps were removed for histological/immunohistochemical analysis and measurement of oxidative stress parameters. The effects of HRCC on the number of leukocytes in BALF, muscle fiber diameter, central nuclei, and nuclear factor kappa B (NF-κB) were reverted after combined physical training. In addition, increased myogenic factor 5, tumor necrosis factor alpha (TNFα), reduced transforming growth factor beta (TGF-β), and nitrate levels were observed after physical training. However, the reduction in superoxide dismutase and glutathione/glutathione oxidized ratio induced by HRCC was not affected by the training program. These results suggest the important changes in the skeletal muscle brought about by HRCC-induced alteration in the muscle redox profile. In addition, combined physical exercise contributes to remodeling without disrupting muscle morphology.